2018
DOI: 10.5455/ajvs.293575
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Symbiotic Drenching Mixture on the Ingestive Behavior, Productive Performance, Blood Biochemical Parameters and Carcass Traits of Growing Rabbits

Abstract: Key words:Rabbits, symbiotic, ingestive behavior, blood biochemical, growth performance.Stressors that originated from intensive housing of young rabbits during the growing period have bad effects on rabbit performance and health status. A total of forty-five apparently healthy New Zealand White rabbits were used to investigate the effect of drenching of symbiotic mixture on the behavior, productive performance, blood biochemistry and carcass criteria of growing rabbits. They were allocated into two groups} 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…Synbiotics are a synergistic mixture of probiotics and prebiotics, as they support growth and survival of probiotics and boost their health benefits in the gut. Studies proved that dietary synbiotics enhanced growth performance in growing rabbits (Hassanin et al, 2015;Ali and Hassan, 2018;Kurchaeva et al, 2020;Nwachukwu et al, 2021). Kurchaeva et al (2020) reported that dietary synbiotic (1 g/kg diet) enhanced growth performance (BW and BWG), carcass traits (cooled carcass weight and dressing %), meat chemical composition (increased meat protein, Na, Ca, K, and P contents, while reduced meat fat content), meat physical traits (water-holding capacity, moisture binding capacity, fat holding capacity ability, emulsifying ability, and emulsion stability).…”
Section: Synbioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synbiotics are a synergistic mixture of probiotics and prebiotics, as they support growth and survival of probiotics and boost their health benefits in the gut. Studies proved that dietary synbiotics enhanced growth performance in growing rabbits (Hassanin et al, 2015;Ali and Hassan, 2018;Kurchaeva et al, 2020;Nwachukwu et al, 2021). Kurchaeva et al (2020) reported that dietary synbiotic (1 g/kg diet) enhanced growth performance (BW and BWG), carcass traits (cooled carcass weight and dressing %), meat chemical composition (increased meat protein, Na, Ca, K, and P contents, while reduced meat fat content), meat physical traits (water-holding capacity, moisture binding capacity, fat holding capacity ability, emulsifying ability, and emulsion stability).…”
Section: Synbioticsmentioning
confidence: 99%
“…Hashem et al (2021) indicated that dietary nanoencapsulated Alginate-Synbiotic (11 × 10 12 CFU Saccharomyces cerevisiae yeast + 0.15 g Moringa oleifera leaf extract/kg diet) enhanced gut microbiota ecosystem (increased yeast cells and Lactobacillus counts and reduced Salmonella and Coliforms counts in small intestine and cecum) and increased lengths of small intestine and cecum in comparison with control. Ali and Hassan (2018) concluded that administration of synbiotic increased final BW, BWG, serum concentrations of total protein, albumin, and globulin, feeding behaviour duration, drinking behaviour frequency, and drinking behaviour duration of growing rabbits. Moreover, Sarfraz et al (2019) proved that dietary synbiotic (Lactobacillus acidophilus, FOS, and IMO) by doses of 2, 4, or 6 g/100 g diet had a significant hypolipidaemic potential in form of reducing serum concentrations of total cholesterol, triglycerides, LDL, and VLDL levels, whereas HDL level was increased.…”
Section: Synbioticsmentioning
confidence: 99%